The association between functional status and physical pain with depressive symptoms after a stroke event: A cross-sectional analysis of the China Health and Retirement Longitudinal Study 2018 - Zhao, William Yang; Zhang, Luwen; Wan, Yingfeng; Chen, Xiaoying; Jin, Yinzi; Zhang, Lin; Sum, Grace; Katar, Ameera; Song, Lili; Anderson, Craig S. (Frontiers in Psychiatry, 2022)
Background Stroke is a major cause of mortality and long-term physical and cognitive impairment. This study aims to: (1) examine the prevalence of depressive symptoms, disability and pain among Chinese adults with stroke; (2) test the associations of functional limitations and body pain with occurrence of depressive symptoms; (3) investigate gender and urban-rural disparities in these associations. Methods This study utilized the data from the China Health and Retirement Longitudinal Study in 2018, involving 969 patients with stroke among 17,970 participants aged ≥ 45 years. Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression (CES-D) Scale. We performed multivariable logistic regression models to estimate the associations between activities of daily life (ADL), instrumental activities of daily life (IADL) and pain with depressive symptoms. Results Depressive symptoms were found among 40.2% of stroke patients, with a higher prevalence in females (48.2%) than males (32.7%). Prevalence of ADL limitations, IADL limitations and pain among stroke patients were 39.2, 49.8 and 14.0%, respectively. ADL and IADL limitations and pain were more prevalent among females and residents in rural areas. Multivariable regression analyses showed a significant association between ADL limitation (OR = 1.535, 95% CI = 1.168, 2.018), IADL limitation (OR = 1.666, 95% CI = 1.260, 2.203) and pain (OR = 2.122, 95% CI = 1.466, 3.073) with depressive symptoms. Stratified analyses revealed stronger associations among urban residents. Females had a higher association of ADL and IADL with depressive symptoms but similar in that of pain to the males. The impact of ADL and IADL in male patients is higher than in females, but the impact of pain on depressive symptoms is higher in female patients. Conclusion Depressive symptoms are common amongst post-stroke patients in China and are significantly associated with functional disability and physical pain. Our findings have implications for practitioners on the early assessment of pain and depression after stroke. Future research should explore effective intervention measures for physical-mental stroke complications.